Exploring the Supportive Classroom Environment in Relation with Students’ Willingness to Communicate in English - Septian Maulana; Nita Kaniadewi (Jurnal Studi Guru dan Pembelajaran, 2025)
This study is concerned with the interplay between the classroom atmosphere and an EFL senior high school learner's willingness to communicate (WTC) in English. Information was gathered from 153 students in Bekasi, Indonesia, using two questionnaires: the Classroom Environment Survey and the Willingness to Communicate Scale. From a descriptive point of view, students reported that their classes were supportive overall, while they exhibited medium levels of English WTC. Correlation analyses revealed a moderate yet significant positive relationship (r = 0.413, p < 0.01) between the classroom environment and WTC. Feeling supported by peers and teachers generates a sense of personal confidence within students to communicate in English. Findings suggest the importance of creating a conducive classroom atmosphere to foster and enhance students' confidence and willingness to speak in English. Practical recommendations aimed at improving classroom interaction for promoting language use among EFL students are proffered in this study for future teachers. s